A universal electrochemical lithiation–delithiation method to prepare low-crystalline metal oxides for high-performance hybrid supercapacitors. Issue 48 (13th September 2021) - Wu, Zhuo-Dong; Chen, De-Jian; Li, Long; Wang, Li-Na
Abstract : The electrochemical performance of transition metal oxides (TMOs) for hybrid supercapacitors has been optimized through various methods in previous reports. Abstract : The electrochemical performance of transition metal oxides (TMOs) for hybrid supercapacitors has been optimized through various methods in previous reports. However, most previous research was mainly focused on well-crystalline TMOs. Herein, the electrochemical lithiation–delithiation method was performed to synthesise low-crystallinity TMOs for hybrid supercapacitors. It was found that the lithiation–delithiation process can significantly improve the electrochemical performance of "conversion-type" TMOs, such as CoO, NiO, etc. The as-prepared low-crystallinity CoO exhibits high specific capacitance of 2154.1 F g −1 (299.2 mA h g −1 ) at 0.8 A g −1, outstanding rate capacitance retention of 63.9% even at 22.4 A g −1 and excellent cycling stability with 90.5% retention even after 10 000 cycles. When assembled as hybrid supercapacitors using active carbon (AC) as the active material of the negative electrode, the devices show a high energy density of 50.9 W h kg −1 at 0.73 kW kg −1 . Another low-crystallinity NiO prepared by the same method also possesses a much higher specific capacitance of 2317.6 F g −1 (302.6 mA h g −1 ) compared to that for pristine commercial NiO of 497.2 F g −1 at 1 A g −1 . The improved energy storage performance of the low-crystallinity metal oxides can be ascribed to the disorder of as-prepared low-crystallinity metal oxides and interior 3D-connected channels originating from the lithiation–delithiation process. This method may open new opportunities for scalable and facile synthesis of low-crystallinity metal oxides for high-performance hybrid supercapacitors.